Recreational Use of Nitrous Oxide as a Source of Frostbite Injuries to the Skin: A Review of the Literature and a Case Report - Sebastian Holm; Reza Tabrisi; Johann Zdolsek (European Burn Journal)
Nitrous oxide has a wide range of medical applications, such as being used as an analgesic in general anesthesia, dental procedures, childbirth and sedation. Lately, it has also been employed as an inhalant recreational drug to induce brief euphoria. Recent studies indicate a worldwide rise in the incidence of skin frostbites associated with nitrous oxide use. A scoping review was conducted to synthesize and summarize the existing literature published in English regarding frostbite injuries associated with the recreational use of nitrous oxide. The literature search was carried out in July 2024 using databases such as Embase, Web of Science and PubMed®. From an initial pool of 83 publications, 8 studies were ultimately selected for full-text review as they met our inclusion criteria for analysis. Additionally, we provide a representative clinical case involving a 21-year-old male who experienced frostbite following skin exposure to nitrous oxide. Most publications on nitrous oxide induced frostbites are from recent years, primarily between 2022 and 2024, with the first case documented in 1996. These injuries are mostly observed in young adults, with a female dominance, and are typically localized to the inner thighs. According to the existing literature, the predominant treatment approach is conservative management, with excision and split-thickness skin grafting (STSG) in the second place. This study represents the first literature review summarizing frostbite injuries to the skin from nitrous oxide misuse. There is a need for enhanced preventive measures to raise public awareness and reduce the incidence of frostbite injuries associated with the recreational use of nitrous oxide.